Kartagener Syndrome: A Case Report - Herick Alvenus Willim; Dofi Pebriadi; Eva Lydia Munthe; Harie Cipta; Widi Mujono; Abdul Muin (HM Publisher, 2023)
Kartagener syndrome (KS) is a rare autosomal recessive disorder characterized by a clinical triad of situs inversus, chronic sinusitis, and bronchiectasis. Impaired ciliary motility due to abnormal ciliary structure or function is the main pathophysiological problem in KS. A 38-year-old woman presented to our outpatient clinic with a productive cough, fever, and shortness of breath for 1 month. She has had recurrent episodes of respiratory tract infections since childhood. Clinical investigations revealed situs inversus, sinusitis, and bronchiectasis. She was diagnosed with KS and treated with antibiotics, mucolytics, bronchodilators, and chest physiotherapy. Patients with KS present with chronic recurrent respiratory tract infections due to ineffective mucociliary clearance. Early diagnosis is important to improve prognosis. The main goals in the management of KS are to prevent the progression of the disease, preserve pulmonary function, and improve quality of life.